2005
DOI: 10.1097/01.sla.0000161029.27410.71
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Bile Duct Injuries Sustained During Laparoscopic Cholecystectomy

Abstract: This series represents the largest single institution experience reporting the perioperative management of BDI following LC. Although perioperative complications are frequent, nearly all can be managed nonoperatively. Early referral to a tertiary care center with experienced hepatobiliary surgeons and skilled interventional radiologists would appear to be necessary to assure optimal results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
346
5
33

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(401 citation statements)
references
References 32 publications
17
346
5
33
Order By: Relevance
“…However many authors have failed to identify early repair as an individual risk factor. 12,14,15 In this series, early repair within 3 weeks was associated with the lowest incidence of major complications, as reported in some other series also. 16 Patients with late repairs and repeat surgeries were associated with significantly higher incidence of major complications though timing of repair was not an independent predictor of outcome.…”
Section: Discussionsupporting
confidence: 66%
“…However many authors have failed to identify early repair as an individual risk factor. 12,14,15 In this series, early repair within 3 weeks was associated with the lowest incidence of major complications, as reported in some other series also. 16 Patients with late repairs and repeat surgeries were associated with significantly higher incidence of major complications though timing of repair was not an independent predictor of outcome.…”
Section: Discussionsupporting
confidence: 66%
“…BDI patients comprise a diverse and complex group, and outcome after repair at tertiary referral centres is frequently reported to be favourable. [7][8][9] Outcome in terms of quality-of-life (QoL) after BDI is less frequently reported in the literature, and the results in publications have been conflicting. [10][11][12][13][14][15][16] The SF-36 (36-item Short Form health survey) questionnaire is a widely used and validated QoL instrument that has been used for evaluating QoL after BDI.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported alarming outcomes for BDI repair, and in some series, mortality and morbidity for biliodigestive reconstruction after injury are as high as 8.6 % and 42 % respectively [34]. Even in the event of a successful repair, subsequent morbidity is significant and the sequelae include symptomatic adhesions, recurrent cholangitis, abscess, strictures, secondary biliary cirrhosis, and chronic liver disease [3,[35][36][37][38][39][40].…”
mentioning
confidence: 99%